SISTEM INFORMASI SELEKSI ANGGOTA TIM SEPAK BOLA BERBASIS WEB (STUDI KASUS PERSIJAP JEPARA) (Information Technology and Telematics, 2014)
Abstract Selection is done Persijap Jepara football team is still using it manually, so the football players who came from outside Jepara, especially outside Java is too far away to make the selection on the town of Jepara. This study has resulted in registration system selection in a web-based football team Jepara Persijap displaying a selection of registration along with the video, this application is built using Macromedia Dreamwiver8 use. So far, information about football in this country, particularly the Indonesian Super League Football Competition has not managed computerized. Therefore it is necessary to design the Football League Competition Information Systems Indonesia to provide for the holding of the competition progress Keywords: Information Systems, web, Macromedia Dreamweaver8